Circulating miR-16-5p, miR-92a-3p, and miR-451a in plasma from lung cancer patients: Potential application in early detection and a regulatory role in tumorigenesis pathways - Reis, Patricia P. [UNESP]; Drigo, Sandra A. [UNESP]; Carvalho, Robson F. [UNESP]; Lapa, Rainer Marco Lopez; Felix, Tainara F. [UNESP]; Patel, Devalben; Cheng, Dangxiao; Pintilie, Melania; Liu, Geoffrey; Tsao, Ming-Sound (MDPI, 2020)
Background: Micro(mi)RNAs, potent gene expression regulators associated with tumorigenesis, are stable, abundant circulating molecules, and detectable in plasma. Thus, miRNAs could potentially be useful in early lung cancer detection. We aimed to identify circulating miRNA signatures in plasma from patients with lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSC), and to verify whether miRNAs regulate lung oncogenesis pathways. Methods: RNA isolated from 139 plasma samples (40 LUAD, 38 LUSC; 61 healthy/non-diseased individuals) were divided into discovery (38 patients; 21 controls for expression quantification using an 800-miRNA panel; Nanostring nCounter®) and validation (40 patients; 40 controls; TaqMan® RT-qPCR) cohorts. Elastic net, Maximizing-R-Square Analysis (MARSA), and C-Statistics were applied for miRNA signature identification. Results: When compared to healthy individuals, 580 of 606 deregulated miRNAs in LUAD and 221 of 226 deregulated miRNAs in LUSC had significantly increased levels. Among the 10 most significantly overexpressed miRNAs, 6 were common to patients with LUAD and LUSC. Further analysis identified three signatures composed of 12 miRNAs. Signatures included miRNAs commonly overexpressed in patient plasma. Enriched pathways included target genes modulated by three miRNAs in the C-Statistics signature: miR-16-5p, miR-92a-3p, and miR-451a. Conclusions: The 3-miRNA signature (miR-16-5p, miR-92a-3p, miR-451a) had high specificity (100%) and sensitivity (84%) to predict cancer (LUAD and LUSC). These miRNAs are predicted to modulate genes and pathways with known roles in lung tumorigenesis, including EGFR, K-RAS, and PI3K/AKT signaling, suggesting that the 3-miRNA signature is biologically relevant in adenocarcinoma and squamous cell carcinoma of the lung.
Keywords: Biomarkers; Liquid biopsy; Lung adenocarcinoma; Lung cancer; Lung squamous cell carcinoma; Lung tumorigenesis; MicroRNAs; Pathways; Plasma